Diagnostico por imágenes de Lesiones hepáticas focales Solidas - Csendes , Paula; Fernández A., Manuel (Revista Hospital Clínico Universidad de Chile, 1996)
IMAGING DIAGNOSIS OF FOCAL SOLID LIVER DISEASE. The imaging diagnosis of benign and malign focal solid hepatic disease are analized by the authors.